Analisis Kompetensi Sosial Guru Membentuk Karakter Siswa di SMP Negeri 35 Medan - Eunike Br Simanjuntak; Relly Tamba; Sri Yunita; Stevan Oktureja Pasaribu (Journal on Education, 2023)
Teacher competence is one of the factors that influence the achievement of learning goals and school education. Teachers must have skills that can be used in the classroom, including teacher social skills. The purpose of this study was to describe the social competence of class VIII SMP teachers. This type of research is descriptive qualitative research. The results showed that the competence of grade VIII junior high school teachers was in the "very good" category and in accordance with the components of the teacher's social competence, namely being inclusive, acting objectively and not based on gender, religion, race, physical condition, family background and socioeconomic status. Communicate effectively, empathetically and politely with fellow teachers, educators, parents and the community. Adjustment is not a task in the socio-culturally diverse Republic of Indonesia. The conclusion of this study is that grade VIII junior high school teachers already have very good competence and are in accordance with the Social Competency Indicators of Permendiknas No. 16 of 2007 in terms of academic qualification requirements and teacher competence.